The Informal Caregivers of Aboriginal Seniors: Perspectives and Issues - Parrack, Sarah; Joseph, Gillian M. (First Peoples Child & Family Review, 2007)
Over 1 million Canadians aged 45-64 provide care to seniors with disabilities or physical limitations, and 70% are also employed – many full-time. Yet often policy assumes that all communities face the same eldercare challenges despite regional and cultural distinctions. This paper highlights what little is known about Aboriginal informal eldercare providers. Trends in health, employment and migration continue to raise concerns about the availability of caregivers, particularly in isolated communities. Difficulties accessing services increases the burdens of caregivers both locally and at a distance. More information about the context of Aboriginal eldercare is sorely needed.